Utilizing Plotagon Animation to Improve Students’ Enthusiasm in English Language Subjects - Ika Purnama Sari; Khairun Niswa; Anita Purba; Iin Parlina; Paramita Kusumawardhani; Rizky Khairunnisa Sormin (Journal of Education and Learning Research, 2024)
his research aims to increase students' enthusiasm for learning English using Plotagon animation. Greeting material is a phenomenal and exciting material to be discussed. This research was carried out at STIKOM Tunas Bangsa Pematangsiantar. This study's population was 1st-semester students majoring in informatics engineering, totaling 34 students. The data was obtained using a questionnaire. The data analysis technique calculates a questionnaire's results about how enthusiastic the students are about learning English with the Plotagon animation. After the data was collected, it was analyzed using quantitative descriptive methods. This research shows that more than 85% of students are interested in learning plotagon animation. Students are also more curious about learning Plotagon animation.